Chemical composition and in vitro evaluation of antioxidant, antimicrobial, and enzyme inhibitory activities of Erucaria uncata and Thymeleae hirsuta. (October 2020) - Djermane, Nadia; Gali, Lynda; Arhab, Rabah; Gherraf, Noureddine; Bensouici, Chawki; Erenler, Ramazan; Gok, Mesut; Abdessamed, Amina
Abstract: The phytochemical analysis and in vitro investigation of the pharmacological effects of crude extracts and essential oils (EO) of Erucaria uncata and Thymelaea hirsuta was carried out. The Results showed that T.hirsuta had higher contents in phenolic compounds than E.uncata . Analysis by gas chromatography combined with mass spectrometry (GC/MS) of the EOs showed that α-Cadinol (24.69%), Delta.-Cadinene (18.39%) and tau.-Muurolol (18.28%) were the main components of E. uncata EO, while tetradecanal (12.83%), palmitic acid (9.97%), three-channel (8.64%), dodecyltetraglycol (7.77%) exhibited the dominant components of T. hirsuta EO. The extracts from E. Uncata and T. hirsuta had moderate antioxidant and antimicrobial activities. In addition, the extracts showed no inhibitory effect on acetylcholinesterase, but they exhibited interesting inhibition against BChE in particular the DCM extract of T. hirsuta, which gave an IC50 of 2.98 ± 0.86 μg/mL. The EO of T. hirsuta also displayed a remarkable inhibitory effect on α-glucosidase (IC50  = 15.42 ± 2.77 μg/mL) followed by the methanol extract (IC50  = 33.11 ± 3.54 μg/mL), while for E. uncata only the methanol extract and EO showed a moderate inhibitory effect (IC50  = 820.14 ± 8.68 μg/mL and 77.45 ± 0.22 μg/mL, respectively).Following these outcomes, the different effects exerted by the two plants could be due to the presence of different compounds and therefore they can be considered as an important source of bioactive compounds. Graphical abstract: Image 1 Highlights: Erucaria uncata essential oil analysis by GC/MS showed the dominance of sesquiterpenes. High levels of phenolic compounds were recorded with Thymelaea hirsuta . Crude extracts and EOs from the two plants exhibited moderate antioxidant and antibacterial activities. Both plants have no effect on AChE but have shown a remarkable inhibitory effect on BChE. Thymeleae hirsuta showed an important capacity to inhibit α-glucosidase.